Monitoring Water Sources for Environmental Reservoirs of Toxigenic Vibrio cholerae O1, Haiti - Alam, Meer T. (Centers for Disease Control and Prevention, 2014)
An epidemic of cholera infections was documented in Haiti for the first time in more than 100 years during October 2010. Cases have continued to occur, raising the question of whether the microorganism has established environmental reservoirs in Haiti. We monitored 14 environmental sites near the towns of Gressier and Leogane during April 2012–March 2013. Toxigenic Vibrio cholerae O1 El Tor biotype strains were isolated from 3 (1.7%) of 179 water samples; nontoxigenic O1 V. cholerae was isolated from an additional 3 samples. All samples containing V. cholerae O1 also contained non-O1 V. cholerae. V. cholerae O1 was isolated only when water temperatures were ≥31°C. Our data substantiate the presence of toxigenic V. cholerae O1 in the aquatic environment in Haiti. These isolations may reflect establishment of long-term environmental reservoirs in Haiti, which may complicate eradication of cholera from this coastal country.